1960
DOI: 10.1172/jci104035
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation for and Experimental Correction of the Abnormal Water Diuresis in Cirrhosis *

Abstract: It is well established that certain patients with hepatic cirrhosis show impaired water diuresis following water loads (1). With this limitation in free water excretion, hyponatremia may develop on average water intakes. It has been asserted and denied that antidiuretic hormone (ADH), secreted in excess or inadequately inactivated, is responsible for the water retention (2, 3). In this study the role of antidiuretic hormone in cirrhosis is reexamined. The results do not support the concept that it plays the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0
1

Year Published

1964
1964
1980
1980

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(46 citation statements)
references
References 19 publications
(24 reference statements)
5
40
0
1
Order By: Relevance
“…Although the mechanism of the abnormal renal function was not clear, this animal model was shown to bear several close similarities to human pathophysiology observed in patients with liver disease. Thus, patients with cirrhosis of the liver may demonstrate enhanced renal reabsorption of sodium, delayed excretion of a water Received for publication 16 October 1974 and in revised form 30 December 1974. load, ascites, edema, and impaired urinary concentrating ability (4)(5)(6)(7)(8). Similar abnormalities were demonstrated in clearance studies in dogs with common bile duct ligation (3).…”
supporting
confidence: 61%
“…Although the mechanism of the abnormal renal function was not clear, this animal model was shown to bear several close similarities to human pathophysiology observed in patients with liver disease. Thus, patients with cirrhosis of the liver may demonstrate enhanced renal reabsorption of sodium, delayed excretion of a water Received for publication 16 October 1974 and in revised form 30 December 1974. load, ascites, edema, and impaired urinary concentrating ability (4)(5)(6)(7)(8). Similar abnormalities were demonstrated in clearance studies in dogs with common bile duct ligation (3).…”
supporting
confidence: 61%
“…As these authors point out, an inhibitory effect of mannitol in the descending limb of the loop is not necessarily incompatible with clearance studies which have demonstrated that mannitol infusions increase free water clearance. In view of this observation, the clearance studies of Bell et al (41) and of Schedl and Barrter (42) could be reinterpreted to imply that the major site of salt and water retention in edematous patients is in the loop of Henle.…”
Section: Methodsmentioning
confidence: 99%
“…Since a depression of the glomerular filtration rate is usually associated with hypovolemia, it was thought earlier that this was responsible for the concomitant urinary suggested that volume depletion induces an increase in sodium reabsorption by the nephron at a site proximal to the diluting and concentrating segments. Patients with congestive heart failure, decompensated cirrhosis or severe salt depletion have been shown to have an inability to excrete a water load, due to an impairment in urinary diluting ability (14,16,17). Concentrating ability is similarly impaired by acute or chronic sodium depletion in a way which cannot be explained by a decrease in filtered load (1)(2)(3) is subject to the errors involved in the accuracy of the measurement of GFR in individual nephrons.…”
Section: Discussionmentioning
confidence: 99%
“…Salt deprivation, congestive heart failure, and decompensated cirrhosis are often accompanied by a dilutional hyponatremia secondary to a decrease in the ability of the kidneys to excrete free water and dilute the urine (14,16,17). The urinary excretion of calcium and urate, which are chiefly reabsorbed in the proximal tubule, is curtailed by sodium deprivation (29,30).…”
Section: Discussionmentioning
confidence: 99%